Household and firm leverage, capital flows and monetary policy in a small open economy - Mara Pirovano (National Bank of Belgium, 2013)
This paper outlines a framework for analysing the interaction between financial frictions at the household and firm level, liability dollarization and optimal monetary policy in a small, open economy subject to productivity and capital inflow shocks. It is found that, first, for the shocks under review, the extent of co-movement of financial variables pertaining to entrepreneurs and homeowners crucially depends on the degree of exchange rate flexibility. Second, for a central bank not concerned with financial stability, reacting to inflation and output is considered optimal. Third, including financial stability in the central bank's objectives results in an optimal monetary policy rule reacting to exchange rate depreciation, but not to credit growth, even in the case of large capital inflow shocks. In fact, reacting to credit growth reinforces the initial shock, increasing financial imbalances.
Keywords: E44; E47; E52; F41; F47; 330; DSGE model; capital inflows; financial frictions; liability dollarization; financial stability; Kapitalimport; Schock; Flexibler Wechselkurs; Geldpolitik; Dynamisches Gleichgewicht